Study and analysis induction heating cooker using high frequency resonant converter / Mohammad Saidin - Saidin, Mohammad (2009)
This project studies the concept of resonant converter for induction cooker. Analysis is also performed on topologies of resonant converter, namely half-bridge resonant converter and quasi resonant converter. On top of this, methodology of controlling power intensity is furthered analysed and discussed. In order to validate the analysis result, case study on existing induction cooker using quasi resonant converter is also been performed.